Correction: Heritage, geographical scale and didactic potentiality: Students and teachers' perspectives. - Ana Isabel Ponce Gea; Carlos Martínez Hernández; María Luisa Rico Gómez (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0251398.].